Blue Ocean Strategy Analysis PT Astra Agro Lestari Tbk : - Stanley (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study case aimed to analyse the blue ocean strategy of PT Astra Agro Lestari Tbk. PT Astra Agro Lestari Tbk is an oil company that is needed by many people for any function. The company's line of business is in the fields of agriculture. To achieve the aims and objectives above, the company can carry out business activities in the fields of agriculture and animal husbandry by building oil palm fruit plantations and breeding and cultivating beef cattle. Then in the trade sector, the company carries out large trade in fruit containing oil and large trade in vegetable oils and fats for the processing industry. PT Astra Agro Lestari Tbk has a crude palm oil industry, a palm oil cooking oil industry and an artificial fertilizer industry mixed with primary macro nutrients and carries out transportation where it receives motorized transportation services for general goods and motorized transportation for special goods and services and the last activity is other management consulting activities.